The Problem of Messiah in the Mind of Semitic Religion - Pangeran Manurung (Theological Journal Kerugma, 2018)
Broadly speaking, the subject of the Christology that is still worth talking about in the academic pulpit is the title "Messiah" carried by Jesus Christ. In general, the Judeo-Islamic community and some Christians are still dilemma in positioning Jesus, especially regarding the worthiness of Jesus Christ to be accepted as the Messiah. Placing Jesus Christ in the right place for all three of these great religions has proven to be no easy matter. Especially for Judeo-Islam, Christians generally accept Jesus Christ as the Messiah. On the contrary for Jews and Islam. Some Jews gave rise to a half-movement of Judaism and half-Christians in terms of seeing Jesus as the Messiah. Likewise with Islam. Here are some of the main problems. Keynote: Messiah, Jesus Christ, Semitic Religion.